The LDL apolipoprotein B-to-LDL cholesterol ratio: association with cardiovascular mortality and a biomarker of small, dense LDLs - Silbernagel, Günther; Scharnagl, Hubert; Saely, Christoph H.; Reinthaler, Markus; Rief, Martin; Kleber, Marcus E.; Larcher, Barbara; Chapman, John; Schaefer, Juergen R.; Drexel, Heinz; März, Winfried (Biomedicines, 2022)
Background and Objective: Small, dense low-density lipoproteins (LDLs) are considered more atherogenic than normal size LDLs. However, the measurement of small, dense LDLs requires sophisticated laboratory methods, such as ultracentrifugation, gradient gel electrophoresis, or nuclear magnetic resonance. We aimed to analyze whether the LDL apolipoprotein B (LDLapoB)-to-LDL cholesterol (LDLC) ratio is associated with cardiovascular mortality and whether this ratio represents a biomarker for small, dense LDLs. Methods: LDLC and LDLapoB were measured (beta-quantification) and calculated (according to Friedewald and Baca, respectively) for 3291 participants of the LURIC Study, with a median (inter-quartile range) follow-up for cardiovascular mortality of 9.9 (8.7-10.7) years. An independent replication cohort included 1660 participants. Associations of the LDLapoB/LDLC ratio with LDL subclass particle concentrations (ultracentrifugation) were tested for 282 participants. Results: In the LURIC Study, the mean (standard deviation) LDLC and LDLapoB concentrations were 117 (34) and 85 (22) mg/dL, respectively; 621 cardiovascular deaths occurred. Elevated LDLapoB/LDLC (calculated and measured) ratios were significantly and independently associated with increased cardiovascular mortality in the entire cohort (fourth vs. first quartile: hazard ratio (95% confidence interval) = 2.07 (1.53-2.79)) and in statin-naïve patients. The association between calculated LDLapoB/LDLC ratio and cardiovascular mortality was replicated in an independent cohort. High LDLapoB/LDLC ratios were associated with higher LDL5 and LDL6 concentrations (both p < 0.001), but not with concentrations of larger LDLs. Conclusions: Elevated measured and calculated LDLapoB/LDLC ratios are associated with increased cardiovascular mortality. Use of LDLapoB/LDLC ratios allows estimation of the atherogenic risk conferred by small, dense LDLs.